INSSEPT: An open-source relational database of seismic performance estimation to aid with early design of buildings. Issue 4 (November 2020) - Zaker Esteghamati, Mohsen; Lee, Jeonghyun; Musetich, Matthew; Flint, Madeleine M
Performance-based earthquake engineering (PBEE) assessments are data-, effort-, and time-intensive, usually requiring a detailed structural model and limiting their integration with early design. Decades of research have produced an abundance of PBEE assessments for different structural systems and building taxonomies. The results of these PBEE studies can be assimilated to approximately represent the seismic design space for new structures and to identify possibly optimal systems with low effort. This article introduces an open-source relational database, Inventory of Seismic Structural Evaluations, Performance Functions and Taxonomies for Buildings (INSSEPT) that contains PBEE assessment of 222 buildings from literature and is freely available to the public in a natural hazard repository. INSSEPT is organized to provide a curated building taxonomy and PBEE data to readily serve as a resource for early design or PBEE-derived regional seismic risk analysis.